DMSP/OLS night-time light intensity as an innovative indicator of regional sustainable development. Issue 4 (16th February 2019) - Li, Chang; Li, Guie; Tao, Guofeng; Zhu, Yujia; Wu, Yijin; Li, Xi; Liu, JIngyi
ABSTRACT: This study proposes the use of DMSP/OLS night-time light data as a surrogate measure for comprehensive indicators to evaluate regional sustainable development. First, Sustainable Development Indicators (SDIs) were selected from annual multiple scores of sustainable development based on Principal Component Analysis (PCA), and annual Sum of Lights (SOL) of the study region were extracted for each year. Next, three time-series-based regression models were applied to the multiple score and SOL to verify their correlation. Lastly, based on time series, DMSP/OLS data is used to estimate regional sustainable development. Experiments using Shandong, Hubei, Henan, Anhui, Jiangxi, and Hunan Provinces, China as test datasets demonstrate that SOL is strongly related to multiple scores ( R 2 ≥ 0.8). Moreover, the PCA results of sustainable development agree with the actual regional development conditions. In theory, night-time light can explain the key factors of SDIs. Hence, it is feasible to study regional sustainable development using SOL instead of SDIs.